Reference Values for the Closed Kinetic Chain Upper Extremity Stability Test (CKCUEST) for Collegiate Baseball Players - Roush, James R. (Sports Physical Therapy Section, APTA, 2007)
BACKGROUND: The Closed Kinetic Chain Upper Extremity Stability Test (CKCUEST) is a tool developed and used in the clinic to evaluate progress during upper extremity rehabilitation. A need exists for reference values of CKCUEST for use in a clinical setting. OBJECTIVES: To calculate reference values for the CKCUEST that may assist clinicians in developing goals and objectives for male collegiate baseball players who are recovering from injuries to the upper extremity. To determine if differences exist in scores according to playing position. METHODS: The sample consisted of 77 collegiate, male baseball players between the ages of 18 and 22 who reported no recent history of injuries to the shoulder, elbow, or the hand-wrist complex. The CKCUEST was administered three times to the athletes and the number of touches when performing the CKCUEST during the 15-second test was measured and recorded. An average of the three tests was used for data analysis. RESULTS: No significant differences existed according to playing position. The data did not differ from the normal distribution; therefore, reference values were calculated and reported for use by clinicians in development of goals and objectives for this population. DISCUSSION AND CONCLUSION: The CKCUEST appears to be a clinically useful test for upper extremity function.